The Psychology of Intuition: Theoretical Cognitive Mechanisms and Empirical Insights - Dhillon, Sukhmani Kaur (Journal of Neonatal Surgery, 2025)
This paper uses theoretical analysis and empirical synthesis to explore the intuition's psychological foundations. Many times, intuitions are perceived as automatic and non-conscious processes which are automatic. But for decades, it has been given very little research or no due consideration in scientific fields. There are many empirical and theoretical supports from cognitive psychology, neuroscience, as well as decision-making science, which acknowledge the role of intuitions. These highlights are in terms of moral reasoning in difficult situations, creativity, as well as decision-making skills in trying or uncertain times. This research paper examines essential theories which support intuitions. For instance, it includes the dual-process model, cognitive and emotional mechanisms in decision making, neurological sciences, and heuristic theories underlying intuitions. Furthermore, along with this, empirical support is also given. Empirical support includes clinical decision-making, creative insights, and morals-based psychology. Both theory and empirical research discuss the reliability and validity of intuitions in terms of the real-world context .